Cardioprotective Effects of Ghrelin in Heart Failure: From Gut to Heart - Khatib, Mahalaqua Nazli (Heart Views, 2014)
Chronic heart failure (CHF) is a major cause of morbidity and mortality. Cardioprotective effects of ghrelin, especially in its acylated form have been demonstrated in heart failure (HF) models and exploratory human clinical studies. Hence, it has been proposed for the treatment of HF. However, the underlying mechanism of its protective effects against HF remains unclear. Future researches are needed to evaluate the efficacy of Ghrelin as a new biomarker and prognostic tool and for exploring its therapeutic potential in patients suffering from CHF.